2013
DOI: 10.1111/ggi.12047
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing patterns of proton pump inhibitors in older hospitalized patients in a Scottish health board

Abstract: Inappropriate PPI prescribing is common in frail older hospitalized patients, and might increase the risk of drug-drug interactions. Polypharmacy and comorbidity were independently associated with inappropriate PPI prescribing in this group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 38 publications
4
30
0
Order By: Relevance
“…4 In our study, out of 80 PPI discharge prescriptions, 64 were pre-admission prescriptions that patients were taking for various reasons, such as previous history of upper GI symptoms (which had occurred from several years up to two decades earlier), peptic ulcer disease, GIP of low-dose aspirin, and non-specified reasons.…”
Section: Figure 2: Summary Of Proton Pump Inhibitor Indicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…4 In our study, out of 80 PPI discharge prescriptions, 64 were pre-admission prescriptions that patients were taking for various reasons, such as previous history of upper GI symptoms (which had occurred from several years up to two decades earlier), peptic ulcer disease, GIP of low-dose aspirin, and non-specified reasons.…”
Section: Figure 2: Summary Of Proton Pump Inhibitor Indicationsmentioning
confidence: 99%
“…However, all recent studies have reported a very high prevalence of inappropriate PPI prescribing and our result findings are consistent with these studies. 2,3,4,[18][19][20] Finally, as the guidelines recommend periodic assessment for the continued use of PPI, it may be challenging to assess symptoms among the very elderly, frail, and debilitated elderly with dementia and communication issues. This may have posed difficulties for the prescribing physicians in determining the need for a prescription.…”
Section: Figure 2: Summary Of Proton Pump Inhibitor Indicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 40% of elderly adults receive PPIs, and appropriate clinical indications may be lacking for up to 85% of PPIs prescribed. 22,23 Pneumonia is a major cause of death, 24,25 costing in excess of $17 billion per year in the United States alone. 26 It is therefore important to clarify associations between PPIs and pneumonia for short-and long-term exposure, especially in older adults, who may be most at risk from lack of barriers to respiratory infection.…”
mentioning
confidence: 99%
“…Long‐term PPI users had serum magnesium levels (1.95 mg/dL) similar to those of PPI nonusers (2.00 mg/dL; P = .20). A large percentage of elderly adults have been prescribed PPIs . Because PPIs, even though generally considered to be safe, have some adverse effects, their prescription must always be motivated by and based on scientific evidence.…”
mentioning
confidence: 99%